Gastric bypass leads to improvement of diabetic neuropathy independent of glucose normalization: results of a prospective cohort study (DiaSurg 1 study) - Müller, Beat P.; Fischer, Lars; Kenngott, Hannes Götz; Gondan, Matthias; Senft, Jonas; Clemens, Gabriella; Nickel, Felix; Fleming, Thomas; Nawroth, Peter Paul; Büchler, Markus W. (Annals of surgery, 2013)
Objective: - Surprisingly, 40% to 95% of patients with type 2 diabetes mellitus (T2DM) show early remission of hyperglycemia after obesity surgery. It is unknown to what extent other diabetes-associated comorbidities such as distal peripheral neuropathy (DPN) might be influenced by obesity surgery. This pilot study aimed at providing further evidence for the impact of Roux-en-Y gastric bypass (RYGB) on both glycemic control and DPN in nonseverely obese patients with insulin-dependent T2DM. - Methods: - In the present prospective cohort study, 20 patients with long-standing, insulin-dependent T2DM and a body mass index (BMI) between 25 and 35 kg/m2 underwent laparoscopic RYGB. Body mass index, glycosylated hemoglobin (HbA1c), and DPN [quantified by the Neuropathy Symptom Score (NSS) and the Neuropathy Deficit Score (NDS)] were investigated. - Results: - Six months after surgery, the preoperative BMI of 32.8 ± 2.1 kg/m2 (mean ± standard deviation) dropped to 25.6 ± 2.5 kg/m2 (P < 0.001). Preoperative HbA1c levels decreased from 8.5 ± 1.2% to 7.1 ± 1.2% (P < 0.001), with 15% of patients having a normalized HbA1c level lower than 6.2%. Of 12 patients with documented DPN, the median NSS was 8 (range, 0-10) preoperatively and 0 (range, 0-9) postoperatively (P = 0.004), with 8 patients scoring an NSS of 0. The median NDS was 6 (range, 2-8) preoperatively and 4 (range, 0-8) postoperatively (P = 0.027), with 1 patient scoring an NDS of 0. All patients had an improvement or normalization in either 1 or both scores. - Conclusions: - As expected, BMI and HbA1c levels improved significantly after RYGB. More interestingly, neuropathy scores, such as NSS and NDS, improved significantly early after surgery. Symptomatic neuropathy was completely reversible in 67% of the patients. These findings add further evidence to the fact that RYGB might be a valuable treatment option not only for improving glycemic control but also for reducing diabetes-associated comorbidities, such as DPN. This points to a complex metabolic effect of RYGB that exceeds glucose normalization. However, the results still need to be confirmed in controlled trials.